Pengaruh Penggunaan Gadget Terhadap Prestasi Belajar bagi Mahasiswa Semeter III Prodi PAI Jurusan Tarbiyah Fakultas Tarbiyah dan Tadris UIN FAS Bengkulu - Erlizah; Sukarno; masrifa Hidayani (Yayasan Darusssalam Bengkulu, 2024)
The Effect of Using Gadget on Learning Achievement for Semester III Students of PAI Study Program, Tarbiyah Department, Tarbiyah and Tadris Faculty of UIN FAS Bengkulu. Gadget is a technological tool that is currently developing rapidly and has special functions, including smartphones or Android or tablets. This study aims to determine the use of gadgets in the learning process of third semester students of Islamic Studies Study Program Tarbiyah Department, Tarbiyah and Tadris Faculty of IAIN Bengkulu, to determine the effect of gadgets on student achievement in third semester PAI Study Program Tarbiyah Department, Tarbiyah and Tadris Faculty of IAIN Bengkulu, and to determine learning achievement. third semester student of PAI Study Program Department of Tarbiyah, Faculty of Tarbiyah and Tadris IAIN Bengkulu. This type of research is a descriptive quantitative research. Data collection techniques used are observation, questionnaires, documentation. The population in this study were all students of PAI class of 2020 semester III. The data obtained were analyzed using data analysis techniques consisting of validity test, reliability test, normality test, homogeneity test, linearity test, and the analysis used was simple linear regression analysis, t test and coefficient of determination (R)2. From the output processed through SPPS16, it can be seen that t_count = 3.290 with a significant value of 0.003 <0.05 and with a significance level of 5% two-party test and df = N-1-1 = 2.074. it can be concluded that the hypothesis H0 is rejected Ha is accepted with a significant 5% meaning that the variable use of gadgets has a significant influence on the learning achievement of second semester students of the Study Program (PAI) Faculty of Tarbiyah and Tadris UIN FAS Bengkulu, by 33% and the remaining 67% is influenced by factors others that have not been studied by researchers.